An Overview Of The Regulations Of Corporate Social Responsibility (CSR) Labelled Product - Zaid, Zaid (Indonesia Law Review, 2022)
Over the last 5 years, Indonesia has experienced an emergency of illegal products. Most of them are imported products that do not have adequate labeling standards which can adversely affect both domestic or national trade and stakeholders. On the other hand, product labels are one of the most effective ways to detect the legality, safety, and warranty of a product. This article aims to explore and analyze how the role of product labels can protect and cover social interests. In addition, this research also tries to observe how ethics and laws or regulations regulate product labels to provide a moral foundation and legal certainty and ensure that all interests are maintained. The findings of this study imply that product labeling is a must in an ethical review as well as a legal obligation in order to achieve a fair trade by safeguarding and ensuring the interests of stakeholders. The scope of the law and social responsibility from product labels is not only for humans which includes the protection of social or consumer welfare but also includes the planet which includes the protection of the environment, to animals which include the protection of animal welfare.